Maternal Plasma Metabolomic Profiles in Spontaneous Preterm Birth: Preliminary Results - Barbara Lizewska; Joanna Teul; Pawel Kuc; Adam Lemancewicz; Karol Charkiewicz; Joanna Goscik; Marian Kacerovsky; Ramkumar Menon; Wojciech Miltyk; Piotr Laudanski (Mediators of Inflammation)
Objective. To profile maternal plasma metabolome in spontaneous preterm birth. Method. In this retrospective case-control study, we have examined plasma of patient with preterm birth (between 22 and 36 weeks of pregnancy (n=57)), with threatened preterm labor (between 23 and 36 weeks of pregnancy (n=49)), and with term delivery (n=25). Plasma samples were analysed using liquid chromatography quadrupole time-of-flight mass spectrometry (LC-Q-TOF-MS) in positive and negative polarity modes. Results. We found 168 differentially expressed metabolites that were significantly distinct between study groups. We determined 51 metabolites using publicly available databases that could be subdivided into one of the five groups: amino acids, fatty acids, lipids, hormones, and bile acids. PLS-DA models, verified by SVM classification accuracy, differentiated preterm birth and term delivery groups. Conclusions. Maternal plasma metabolites are different between term and preterm parturitions. Part of them may be related with preterm labor, while others may be affected by gestational age or the beginning of labor. Metabolite profile can classify preterm or term delivery groups raising the potential of metabolome as a biomarker to identify high-risk pregnancies. Metabolomic studies are also a tool to detect individual compounds that may be further tested in targeted researches.